SOME REMARKS ON THE WORK OF STANISŁAW BRZOZOWSKI WITHIN THE SPACE OF POSTCOLONIAL STUDIES - Krasuski, Krzysztof (Porównania, 2012)
The subject of the article is an innovative thesis that the theory of postcolonial studies should be included into the range of comments on the works of the famous critic: Stanisław Brzozowski (1878–1911). The article presents the arguments which indicate that the context of postcolonial studies is appropriate for interpretation cultural and literal essays as well as novels of Brzozowski – the outstanding representative of Polish modernism. He used to write in the critical period in which Poland was freeing itself from annexation. Brzozowski insisted on necessity of modernization of Polish culture and Polish social life. That is why the notion of postcolonial studies seems to be crucial in analyses and interpretations of Brzozowski’s work.